Mobile radiography units in Balkan Wars. Issue 1 (30th June 2015) - Diamantis, Aristidis; Magiorkinis, E
Abstract : Introduction: It is known that the first radiological units were widely used during war conflicts, whereas the first application of military radiology took place during the Greco-Turkish War in 1897. However, until recently automobile radiology units were assumed to be used for the first time during World War I. Method: Historical archives and reports were researched, and extensive research in available literature was also conducted. Results: The automobile radiology units were purchased from France and were probably constructed under the guidance of Marie Curie (1867–1934). The figure of Dr. Dimitrios Vasilidis (?-1937), a pioneer in Radiology in Greece and the first president of the Hellenic Radiological Society, is highlighted. Discussion: This short historical note describes the first use of a mobile radiology unit during the Balkan Wars (1912–1913), predating its previously presumed first use in World War I. It also briefly highlights the contributions of some notable figures in 20th Century Greek scientific development.